2015
DOI: 10.11131/2015/101188
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptors Features, Functions, and Future

Abstract: In this review, the history of the peroxisome proliferator-activated receptors (PPAR , PPAR / and PPAR) discovery is briefly traced and major features of their structure and posttranslational modifications are presented. Furthermore, an overview of PPAR coactivators and corepressors as well as of endogenous and exogenous ligands is discussed. We have also summarized significant efforts underway to develop more effective and safer PPAR modulators as therapeutic agents to treat diseases such as diabetes, cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 299 publications
(399 reference statements)
0
4
0
3
Order By: Relevance
“…2E, panel iii). Altogether, these data suggested that AA-driven stabilization of PPAR␣ could shift the equilibrium of PPAR␣ toward the active configurations resulting in higher interactions with different co-regulators, thus augmenting activation of PPAR␣-driven transcriptional machinery (45,46).…”
Section: Discussionmentioning
confidence: 86%
“…2E, panel iii). Altogether, these data suggested that AA-driven stabilization of PPAR␣ could shift the equilibrium of PPAR␣ toward the active configurations resulting in higher interactions with different co-regulators, thus augmenting activation of PPAR␣-driven transcriptional machinery (45,46).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, in the cytosol, the protein can interact directly with kinases, i.e., MEK1 and PKC α , and cytochrome c reductase [ 66 69 ]. The advantage of such DNA-independent mechanisms is enrooted at the basis of a relative fast initiation of desired cellular effects, whereas a DNA-dependent mode of action can take hours due to their genomic processing structure [ 70 ]. Therefore, for a fast establishment of a specific M Φ phenotype, the presence of a redox-modified PPAR γ could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Ketiga, kurkumin berperan pula dalam induksi dan ekspresi HO-1 (Heme Oxygenase), subunit glutation dan NAD(P)H:quinone oxidoreductase 1. Keempat, kurkumin membuka dan mengaktivasi anion channels, depolarisassi potensial membran sehingga menghasilkan produksi elektron dan memicu insulin keluar dari sel β pankreas (Zhang et al 2013) Mekanisme kurkumin terhadap PPARγ Peroxisome proliferator-activated receptors (PPAR) adalah faktor transkripsi yang berperan penting dalam diferensiasi sel dan beberapa proses metabolisme, terutama pada proses metabolisme lemak dan keseimbangan glukosa di dalam tubuh (Fuentes et al 2013;Lefterova et al 2014;Youssef and Badr 2015). Secara molekuler, aktivasi dari PPAR akan menyebabkan inhibisi faktor transkripsi NF-κB yang akan menurunkan banyak ekspresi gen seperti AP-1, p53, CREB, c-Myc, Wnt13, Dok-4, HMGA1, and c-Src (Grygiel-Górniak 2014).…”
Section: Kurkumin Terhadap Diabetes Tipeunclassified